Mechanical properties, thermal conductivity, and modeling of boron nitride-based polymer composites: A review - T. E. Mokoena; S. I. Magagula; M. J. Mochane; T. C. Mokhena (eXPRESS Polymer Letters)
In the past, polymer materials have been used in electronic devices; however, the major drawback with polymers is their low thermal conductivity, i.e., 0.1–0.5 W/(m・K). Hence, researchers came up with the idea of incorporating conductive fillers into the polymer matrix in order to increase their thermal conductivity. Different conductive materials classified as carbon, metallic, and ceramic-based fillers have been used for this task. However, the drawback with carbon and metalbased fillers is that they reduce the intrinsic insulating properties of polymer materials. Recently, boron nitride (BN), a ceramic-based filler was selected as the conductive filler of choice due to its combined excellent thermal conductivity and electrical insulation as well as high breakdown strength. Due to differences in polarities, boron nitride and polymer matrices form a weak interfacial bond. Therefore, the weak interfacial bond is commonly improved by surface chemical modification of the boron nitride fillers. Furthermore, most of the theoretical models are used to predict the thermal conductivities of boron nitride-polymers composites fitted well with experimental data. This proved that the models could be used to predict the properties of boron nitride composites before their experimental data. The review paper discusses the effect of boron nitride orientation, nanostructures, modification, and its synergy with other conductive fillers on the thermal conductivity and mechanical properties of the polymer matrices.